2002
DOI: 10.1021/cm010504b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Redox Behavior in Copper-Exchanged Sodium Zeolite Y by High-Resolution Powder Neutron Diffraction

Abstract: The results of structural refinements on high-resolution powder neutron diffraction data for copper(II)-and copper(I)-exchanged zeolite Y and for the parent sodium zeolite Y, with composition Na 62 Si 128 Al 64 O 384 , are presented. Rietveld refinement of ambient-temperature data shows that the Cu(I) and Cu(II) cations are located on different sites in the two materials and that the structures differ considerably from that adopted by NaY. In Cu II Y, with composition Cu 33 Na 12 Si 130 Al 62 O 384 , the coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…10,11 XRD studies have shown that site III can be occupied by as many as four Cu/u.c. 10 There are no known H 2 -TPR studies of Cu-Y prepared by vapor-phase exchange with CuCl. While H 2 -TPR spectra of Cu 2+ -exchanged Y have been reported, the assignments of the reduction peaks have been attributed only to general locations described as sodalite, supercage and hexagonal positions.…”
Section: Preparation and Site Occupancy Of Cu-ymentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 XRD studies have shown that site III can be occupied by as many as four Cu/u.c. 10 There are no known H 2 -TPR studies of Cu-Y prepared by vapor-phase exchange with CuCl. While H 2 -TPR spectra of Cu 2+ -exchanged Y have been reported, the assignments of the reduction peaks have been attributed only to general locations described as sodalite, supercage and hexagonal positions.…”
Section: Preparation and Site Occupancy Of Cu-ymentioning
confidence: 99%
“…8 While site III′(III) was not found to be occupied in this study, investigations of Cu-Y prepared by aqueous exchange with either CuCl 2 or Cu(NO 3 ) 2 and subsequent reduction of Cu 2+ to Cu + in H 2 did result in the occupation of this site by Cu + . [10][11][12] Cations in site III are the most accessible to reactants and have been suggested as the active site for NO x reduction by NH 3 . 13,14 The objectives of this work were to determine the site distribution and local structure of Cu + cations in Y zeolite and to assess which types of Cu sites are active for DMC synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Cu ϩ cations must be occupying exposed sites in the Y zeolite framework, such as sites II and III according to the nomenclature of Smith (1971), in order to interact with the sulfur-containing molecules. Recent studies by Fowkes et al (2002) have shown that, upon reduction of Cu(II)-Y, there was a redistribution of cation positions and most of the reduced species (Cu ϩ ) occupied sites I* and II. Lamberti et al (1997) showed similar results for both reduced Cu(II)-Y and Cu(I)-Y prepared, respectively, by ion exchange and gas-phase reaction with CuCl vapor.…”
Section: Adsorbent Activation Copper Autoreduction and Migrationmentioning
confidence: 99%
“…The migration of Cu + cations in zeolites Y induced by the presence of organic molecules (e.g., pyridine, naphthalene, fluorohydrocarbons, butadiene) have been widely discussed [43][44][45][46][47]. It has been demonstrated that the cations placed in S I 0 inside cubooctahedra were more mobile than those in S I sites, which were stabilized by six oxygen atoms.…”
Section: Ethene and Ethyne Adsorptionmentioning
confidence: 99%